1987
DOI: 10.1177/0148607187011004412
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Nutrition Support Team

Abstract: The development of clinical nutrition in the past few years has occasioned a rapid proliferation of hundreds of nutrition support teams across the country. Data available in several surveys of these teams suggest that they are so likely to differ from one another that they scarcely merit a common name. Some standard is clearly needed. A formulation of the essential features that should be found in every NST is presented. In light of this conceptual framework, data on the efficacy of NSTs are discussed. It is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…Patients on HPN must be informed clearly about the definition of infectious complications and given clear and continuous instruction on all aspects of having a CVC, by a well-trained team. [17][18][19] …”
Section: Discussionmentioning
confidence: 99%
“…Patients on HPN must be informed clearly about the definition of infectious complications and given clear and continuous instruction on all aspects of having a CVC, by a well-trained team. [17][18][19] …”
Section: Discussionmentioning
confidence: 99%
“…The presence of a multidisciplinary nutritional care team in regional hospitals can improve the quality of the nutritional support and also reduce the cost (Brown et al 1987;Puntis & Booth 1990). Reported advantages of a nutritional care team include a reduction of central venous catheter sepsis and mechanical catheter-related problems, a decrease in metabolic complications associated with PN, and an increased use of enteral in place of parenteral nutrition (Hamaoui, 1987).…”
Section: Feeds Recommended For Etf Following Bmtmentioning
confidence: 99%
“…Thirty‐six percent reported the dietitian as the leader, 18% the pharmacist, and 4% the nurse. In the 1984 Hamaoui 11 survey, the physician was the team leader 93% of the time, and a 1983 study by McShane and Fox 6 reported that 61% of their respondents designated the team physician as leader.…”
Section: Demographicsmentioning
confidence: 99%